Influence of microstructure control on the combustion behavior of Al–Mo alloy powder - HeFeng Lin; Zhe Zhu; SiNan Feng; LiYan Chen; XiaoXia Wang; DaWen Zeng (Journal of Materials Research and Technology)
Combustion efficiency and energy performance of micron-sized Al powder has been enhanced through alloying. However, as the content of alloying elements increases, the comprehensive energy performance of Al powder does not improve indefinitely, and the energy density often decreases significantly. Therefore, a promising approach to enhance the combustion efficiency of alloy powders is to regulate their microstructure. This study produced three types of Al–Mo alloy powders with distinct morphologies while maintaining consistent composition and microstructure through heat treatment. The research examined the influence of microstructure on the ignition and combustion behavior of these powders. The results indicate that during the low-temperature stage of thermal oxidation, Mo-rich intermetallic compounds initially undergo oxidation of molybdenum, leading to the formation of Al2(MoO4)3. When the temperature reaches 910 °C, the decomposition of Al2(MoO4)3 and the evaporation of volatile MoO3 occur. For large Mo-rich phases, such as block, long rods, or feather-like structures, the evaporation of MoO3 during ignition compromises the integrity of the oxide layer. This tightly connected Mo-rich phase facilitates the penetration of oxygen into the particles, allowing it to react with fresh aluminum. Conversely, When the Mo-rich phase is discontinuously distributed within the alloy as fine, dispersed particles, oxygen will diffuse into the interior through the continuous regeneration of the oxide layer during ignition and react with the Mo present in the Mo-rich phase. The resulting gaseous MoO3 cannot escape through the cracks before being sealed off by newly formed alumina, leading to a buildup of internal gas pressure. This accumulation ultimately results in a microexplosion during the combustion of the alloy particles.